Urban migration and housing during resource booms: The case of Sekondi-Takoradi, Ghana. (November 2019) - Eduful, Alexander K.; Hooper, Michael
Abstract: This paper investigates the relationship between urban migration and housing in the context of an emergent oil boom in Sekondi-Takoradi, Ghana. The paper responds to the relative lack of research on resource boom-driven urbanization, particularly in Africa, and on the way in which urban migration shapes, and is shaped by, housing conditions. The paper analyzes the relationship between housing conditions and urban migrants' choice of residential locations. Drawing on both qualitative and quantitative analysis of data from 322 surveys in two neighborhoods of Sekondi-Takoradi, the paper draws three primary conclusions. First, migrants' choices regarding where they live are premised on neighborhood housing conditions. Second, most migrants are urban-urban migrants which means that the predominant theories of urban growth are poorly equipped to address the urban transformation occurring in Sekondi-Takoradi. Finally, migrants' housing choices have considerable urban form implications, promoting in different contexts both urban densification and urban sprawl. The paper concludes by discussing the implications of these findings in the Ghanaian and wider African contexts.